Spirometry outcomes in survivors of COVID-19 pneumonia - M. A., Ibrahim; Chai, Chee Shee; Johari, B.; R. F., Abdul Kadir; A R., Muttalif; M. F., Abdul Rani (European Respiratory Society Publication, 2022)
Introduction: Acute COVID-19 infection could lead to long COVID, a heterogenous condition which includes the respiratory system. But data on long-term respiratory complications are scarce and limited especially from our part of the world.